Surveillance arbitration in the era of digital policing - Fussey, Peter (Theoretical criminology, 2022)
This article analyses adoptions of innovative technology into police surveillance activities. Extending the nascent body of empirical research on digital policing, the article draws on qualitative interview data of operational police uses of advanced surveillance technologies. Separate illustrative examples are drawn from social media intelligence gathering, digital forensics and covert online child sexual exploitation investigations. Here, surveillance governance mechanisms, often authored in the ‘pre-digital’ era, are deemed ill-fitting to the possibilities brought by new technologies. This generates new spaces of interpretation, where regulatory frameworks become renegotiated and reinterpreted, a process defined here as ‘surveillance arbitration’. These deliberations are resolved in myriad ways, including perceived licence for extended surveillance and, conversely, more cautious approaches motivated by perceived exposure to regulatory sanction.